Interactive Learning Media Based on Educaplay and Local Wisdom to Increase Interest in Learning Christian Religious Education - Dini Desfrianty Viola viola; Telhalia Telhalia; Lelly Sepniwati (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2025)
This study aims to examine the effectiveness of Educaplay-based interactive learning media integrated with local wisdom in increasing students' interest in learning Christian Religious Education at SMAN 3 Palangka Raya. The research uses a quantitative approach with a quasi-experimental design. The research subjects consisted of two groups, namely class XI-9 as an experimental group that used Educaplay media based on local wisdom and class XI-11 as a control group that used conventional learning methods. The integration of local wisdom is carried out through the presentation of materials, illustrations, and learning activities that raise local cultural values, so that learning becomes more contextual and close to students' life experiences. The research data was collected through a learning interest questionnaire that has been tested for validity and reliability. The results of the analysis showed that the use of Educaplay-based interactive learning media and local wisdom significantly increased students' interest in learning. The average learning interest score of the experimental group increased from 49.35 in the pretest to 63.30 in the posttest, while the control group only increased from 51.75 to 53.80. Hypothesis tests using paired sample t-test and independent sample t-test showed significant differences between the two groups. This study concludes that Educaplay-based interactive learning media combined with local wisdom is effective in increasing interest in learning Christian Religious Education. These findings recommend the development of contextual and local culture-based digital learning media to create a more interesting, relevant, and meaningful learning process for students.